Life cycle assessment at a sawmill manufacturing company in Terengganu, Malaysia - Muhammad, Khairul Izzuddin; Sharaai, Amir Hamzah; Abdullah, Sabrina J. Ho (Springer, 2013)
Life Cycle Assessment (LCA) is known as a tool to evaluate and assessing the impacts of products towards the environment. It will include all the process or activities used and waste released into the environment. In detail, LCA involved the collection and evaluation of quantitative data on the inputs and outputs of material, energy and waste flows associated with a product over its entire life cycle. The objective of this study is to identify potential impact of sawmill manufacturing process. This study followed the four phases as stipulated in the International Organization for Standardization (ISO 14040 series of standard) for conducting LCA studies such as goal and scope definition, Life Cycle Inventory analysis (LCI), Life Cycle Impacts Assessment (LCIA), and Interpretation.